Adaptasi Penggunaan Artificial Intelligence (Ai) Pada Mahasiswa - Nenia Nabila Patimah; Mayang Arum Rahmanita; Reza Mauldy Raharja (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the adaptation of the use of Artificial Intelligence (AI) to social behavior, academic integrity, readiness to face the world of work, as well as digital literacy and AI ethics among university students. The research approach used is a qualitative approach with data collection through participant observation and in-depth interviews. The research population consists of students who use AI in their learning and daily activities. The results of this study show that the use of AI by university students has a significant impact on social behavior and academic integrity. In terms of work readiness, students felt that AI can help them learn work skills in the digital era. However, this study also revealed that there are some challenges faced by students in using AI.